Receptor and Channel Heteromers as Pain Targets - Kelly A. Berg; Armen N. Akopian; Amol M. Patwardhan (MDPI AG, 2012)
Recent discoveries indicate that many G-protein coupled receptors (GPCRs) and channels involved in pain modulation are able to form receptor heteromers. Receptor and channel heteromers often display distinct signaling characteristics, pharmacological properties and physiological function in comparison to monomer/homomer receptor or ion channel counterparts. It may be possible to capitalize on such unique properties to augment therapeutic efficacy while minimizing side effects. For example, drugs specifically targeting heteromers may have greater tissue specificity and analgesic efficacy. This review will focus on current progress in our understanding of roles of heteromeric GPCRs and channels in pain pathways as well as strategies for controlling pain pathways via targeting heteromeric receptors and channels. This approach may be instrumental in the discovery of novel classes of drugs and expand our repertoire of targets for pain pharmacotherapy.